Modelo de Referencia para Optimización del Proceso de Gestión de Tecnología de Información y Comunicación en Servitelconet. - Calo Muela, Mario Alcides (2022)
The optimization of processes of an adequate information system has become an important issue for directors and managers of organizations, which is part of the basic elements to stay and endure in the market, therefore the research project had as objective determine a reference model through frameworks, international standards for the optimization of the information and communication technology management process in Servitelconet, it is a study with the highest degree of combination of quantitative, qualitative and comparative design approaches. The population was raised with a sample of 50 expert professionals in the area of systems, communications related to the area of research in the management of information and communication technologies. The state of the art of the literature related to the research topic is established, for the theoretical foundation of the research problem and the content analysis of primary documents related to the topic of reference models for process optimization. comparing the most outstanding processes and components of the frameworks, international standards, and with it the validation technique of expert professionals that allowed validating the model through the mathematical analysis of multiple linear regression, and as a result a reference model was obtained which includes current company processes and their simulation using the Bizagi process modeling tool to verify activities, tasks, and execution times, processes in the management of information and communication technologies.